Electrical system design of airport utilities of General Santos City International Airport - Canizares, Felix R. (Professional Regulation Commission, 2015)
The airport project involves the preparation of the electrical system for an international standard airport that comprises the terminal building, FSS/CFR/Hanger building, power plant, pump house, airfield and runway lighting and navigational equipment. The airport is situated at the 5,994,577 square meter government lot, located at Barangay Fatima, 14 kilometer from the center of General Santos City. The total connected load for the airport is 500 kVA, served by 1,500 kVA transformer at the substation. The substation was provided dedicated solely for the airport connected to the 69 kV primary line and step down to 13.2 kV. The substation was maintained by the SOCOTECO II, the local electric utility. Each building were provided with individual transformer connected to the 1500 kVA transformer through an automatic transfer switch located at the Power plant distribution. The sizes of the transformers are enough to accommodate the future load up to and beyond 2015. Calculation of loads, feeders, busses, breaker, wire gutters, has been design according to the load requirement of each building plus safety and future demand were considered. Wires and cables have been design in accordance to the NEC and PEC. The materials, equipment and all electrical fixtures in this project required product submittals and approved for installation shall passed the International accepted standard such as the ASTM, ANSI, NEC, NFPA, FM/UL, IEEE, other international accepted standard and the Philippine Electrical Code (PEC).